NBIC-Convergence of Machinery and Basic Technologies as the Ecological Factor of Wellbeing; IOP Conference Series: Earth and Environmental Science; Vol. 50 : Ecology and safety in the technosphere: current problems and solutions - Zhironkin S. A. Sergey Aleksandrovich; Kolotov K. A.; Genin A. E.; Agafonov F. V.; Kovalevsky S. A. (2017, 2017)
Title screen